Conceptualising multilingual higher education in policies, pedagogical designs and classroom practices. Issue 1 (2nd January 2016) - Moore, Emilee
ABSTRACT: In striving for internationalisation, government and university policies in Catalonia promote the use of English in classrooms in two ways that often overlap: (1) as a lingua franca aiding the participation of international students and (2) through immersion approaches targeting local students. However, as the findings presented in this article suggest, many of these policies, and resulting higher education curricula and pedagogies, are materialisations of monolingual ideologies that implicitly promote a single language in classrooms. This article begins by contrasting how multilingualism is regulated in legislation, developed in degree programmes and subject plans and enacted in classroom practice at the institutions studied in our research. It then conceptualises plurilingualism and learning to later analyse interactional practices in one subject, involving both local and international students, planned around English only. The analysis centres on the process followed by one student with difficulties in accomplishing a learning task. The aim is to explore the 'nitty-gritty' of students' everyday learning realities to offer alternatives to monolingually conceived multilingual education. The data reveal how the student observed engages her plurilingual repertoire in overcoming obstacles and developing unilingual subject expertise, despite the use of languages other than English not being officially sanctioned. Through this case study of learning-oriented practices, the article is interested in demonstrating how ad hoc, plurilingual language policies enacted in classroom interaction may be more beneficial to learning processes than those officially sanctioned by higher education institutions. The article also offers insights for practical plurilingual pedagogies for universities in linguistically complex regions such as Catalonia and elsewhere.